Degenerative meniscal lesions: Conservative versus surgical management - Akkawi, Ibrahim; Draghetti, Maurizio; Zmerly, Hassan (Acta Biomedica Atenei Parmensis, 2022)
Degenerative meniscal lesions (DML) typically occur in middle-aged or elderly patients without any history of significant acute trauma. Its prevalence increases with age and are associated with knee osteoarthritis (OA). The most frequent orthopaedic treatment is arthroscopic partial meniscectomy (APM) to relieve pain and functional deficit associated with DML. Nevertheless, several randomised controlled clinical trials recommed against APM as the first-line treatment for managing knee pain in patients affected by DML and no radiographic knee OA that should be reserved for cases of failure after 3 month conservative therapy or earlier in patients with signficant knee mechanical symptoms.